Aktifitas Sosial Masyarakat Di Desa Kapita Dalam Mendukung Keberlanjutan Program Pengelolaan Hutan Kemasyarakatan - Suprianto; Amal Said; Helda Ibramin (Journal Of Business, Finance, and Economics (JBFE), 2025)
Community Forest Management (PHKM) is one of the social forestry programs aimed at improving community welfare while maintaining forest sustainability. The sustainability of this program is greatly influenced by the level of community participation. This study aims to analyze the sustainability level of the Community Forest Management (HKM) program based on community participation. The research was conducted in Kapita Village, Bangkala District, Jeneponto Regency, reviewed from social, economic, and ecological aspects from July 24, 2025 to August 31, 2025, using a mixed methods approach. Data were collected through structured interviews with questionnaires involving 134 respondents who were members of forest farmer groups, in-depth interviews, and field observations. The data were analyzed using descriptive statistics, sustainability index calculation, and qualitative triangulation to strengthen the findings. The results show that the social aspect achieved a sustainability index of 63.7% or a score of 3.64, the economic aspect obtained an average score of 3.50, and the ecological aspect reached 3.69, all categorized as moderately sustainable. The Combined Sustainability Index (CSI) of the three aspects was 3.61, placing the PHKM program in the moderately sustainable category. This study concludes that PHKM has had a positive impact on social and economic life as well as environmental conservation.